Tafsir Ilmi Versus Tafsir Ilmi: Ants in Scientific Interpretation Discourses - Shabriyah, Nabila Shema; Miski, Miski (Dialogia, 2023)
This article is based on the Ayat-Ayat Semes ta dan Nalar Ayat-ayat Semesta written by Agus Purwanto and Tafsir 'Ilmi: Animals in the Perspective of the Qur'an and Science published by Lembaga Pentashih Mushaf al-Qur'an (LPMQ) of the Ministry of Religious Affairs of Indonesia in collaboration with the Indonesian Institute of Sciences with a focus on the interpretation of the word "Ant" or al-namlah in QS. al-Naml [27]: 18. Preliminary findings show that the interpretations of Puwanto and LPMQ tend to be different even though they are both based on scientific reasons. There are three questions asked in explaining this. First, what is the construction of Agus Purwanto and LPMQ's interpretation of "Ants" in the Qur'an. Second, why do the two differ in interpretation regarding the theme? Third, what are the implications of these different interpretations on the discourse of ilmi interpretation. This article uses content analysis to show Purwanto's interpretive construction of the diction "Qā lat namlah" in QS. al-Naml [27]:18 means "queen of ants," while LPMQ means "al-namlah" with "an ant," so it has a different meaning. This difference lies in the emphasis of both;  Purwanto emphasizes more linguistic aspects as a support for scientific findings to interpret  "al-namlah" with the queen ant, which also emphasizes that this queen is the leader in the colony. At the same time, LPMQ uses an interpretive logic that does not emphasize "who rules the ants"  These two models of interpretation must be positioned as part of an evolving dynamic of interpretation; Moreover, it is recognized that the same discourse also appeared in explanation in the past although it was more on theological and linguistic aspects.